Legal Validity of Teleconference Witness in Indonesia’s Criminal Justice System - Ramadhan, Muhammad Arief Dwi; Alam, Syariful (Faculty of Law, Universitas Lampung, 2023)
This research is driven by the need to assess the validity and legality of witness statements delivered via teleconference within the Indonesian justice system. As technology and electronic information continue to evolve, teleconferencing emerges as a novel legal tool. Despite this, the Criminal Procedure Code, which is the foundation of criminal procedural law in Indonesia, does not yet include specific provisions regulating this practice. This absence has sparked a polemic, triggering debates and divergent views on whether teleconferencing harms or benefits the parties involved, or whether it serves as an alternative medium to shield witnesses from external interference and threats to their safety. This research concerns the legitimacy of teleconferencing as a valid means of evidence within the Indonesian justice system. The research explores the various arguments for and against the use of witness testimony via teleconference, comparing its implementation in Indonesia with that in other countries. The research methodology employed is normative juridical, focusing on the analysis of legal norms to understand the issues related to the clarity and validity of teleconference-based witness testimony in court proceedings, as well as the associated pros and cons.